1989
DOI: 10.1172/jci114011
|View full text |Cite
|
Sign up to set email alerts
|

Anchorage-independent growth of synoviocytes from arthritic and normal joints. Stimulation by exogenous platelet-derived growth factor and inhibition by transforming growth factor-beta and retinoids.

Abstract: Exuberant tumor-like synovial cell proliferation with invasion of periarticular bone is a feature of rheumatoid arthritis in humans and of streptococcal cell wall (SCW)-induced arthritis in rats. These histologic observations prompted us to examine synoviocytes from arthritic joints for phenotypic characteristics of transformed cells. The capacity to grow in vitro under anchorage-independent conditions is a characteristic that correlates closely with potential in vivo tumorigenicity. In medium supplemented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
174
2
3

Year Published

1990
1990
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 305 publications
(187 citation statements)
references
References 39 publications
8
174
2
3
Order By: Relevance
“…Recent reports have shown that in human cancers, the expression of specific miRNA closely related to the regulation of cell growth and apoptosis differs from that in normal tissues (25,26). RA is characterized by pronounced synovial hyperplasia and by synovial fibroblasts that appear to be transformed (27,28). In animal models of RA, this transformed appearance of RA synoviocytes could be mitigated by transferring the CDK inhibitor genes p16 INK4a and p21 Cip1 into inflamed joints (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Recent reports have shown that in human cancers, the expression of specific miRNA closely related to the regulation of cell growth and apoptosis differs from that in normal tissues (25,26). RA is characterized by pronounced synovial hyperplasia and by synovial fibroblasts that appear to be transformed (27,28). In animal models of RA, this transformed appearance of RA synoviocytes could be mitigated by transferring the CDK inhibitor genes p16 INK4a and p21 Cip1 into inflamed joints (29,30).…”
Section: Discussionmentioning
confidence: 99%
“…Both PDGF and FGF may be produced by macrophages, and they can stimulate DNA synthesis and proliferation of human synovial fibroblasts, without inducing PGE, production (68). Also, PDGF enhances anchorage-independent growth of rheumatoid synovial cells in soft agarose cultures (69). PDGF and IL-1 exhibit complex interactions on cultured rheumatoid synovial cells.…”
Section: Pdgf and Fgfmentioning
confidence: 97%
“…The origins of the cells of the pannus are not clear, but they express inflammation mediators, including neutral proteases (13) and free radicals, leading to DNA damage (2). As a result, fibroblast-like synoviocytes express p53 (14,15), lose contact inhibition (16), and express oncogenes typical of neoplastic cellular growth (17). These cellular phenotypic and protein expression changes may contribute to progressive joint erosion, independent of inflammation (18).…”
mentioning
confidence: 99%